Remembering and Voting: Theory and Evidence from Amnesic Patients - Coronel, Jason C. (2012)
One of the most prominent claims to emerge from the field of public opinion is that citizens can vote for candidates whose issue positions best reflect their own beliefs even when they cannot remember previously learned stances associated with the candidates. The current experiment provides a unique and powerful examination of this claim by determining whether individuals with profound amnesia, whose severe memory impairments prevent them from remembering specific issue information associated with any particular candidate, can vote for candidates whose issue positions come closest to their own political views. We report here that amnesic patients, despite not being able to remember any issue information, consistently voted for candidates with favored political positions. Thus, sound voting decisions do not require recall or recognition of previously learned associations between candidates and their issue positions. This result supports a multiple memory systems model of political decision making.